PENGARUH SISTEM PENGHARGAAN DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU (DI SMAMETHODIST JAKARTA UTARA) - Munir Azhari; Deni Indra Purnama Koto (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2020)
School is an organization consisting of a group of people who work together to achieve predetermined goals. For cooperation to work well, all elements in the organization, especially human resources, must be actively involved and have the drive to achieve goals together. The Principal in this case as the Leader has an important role to mobilize subordinates including himself.In order for human resources to be mobilized in order to achieve organizational goals, it is necessary to implement a reward system. The reward system is a leader's effort in appreciating services for teacher work, so that it can encourage work more actively and potentially. Performance-based reward systems are one of the important control tools used to foster enthusiasm for teachers. With this award, teachers are expected to be more motivated in carrying out their tasks and feel valued their efforts.The purpose of this study was to determine the relationship between the reward system and leadership of the school principal and the performance of teachers in North Jakarta Methodist High School.This study involved teachers in North Jakarta Methodist High School, amounting to 30 people as research samples. Data collection techniques using a questionnaire guided by the Likert scale. Data processing in this study uses the Statistical Product and Service Solution (SPSS) program for Windows version 22. The statistical tests used include validity, reliability, correlation coefficient, determination coefficient, hypothesis testing and multiple regression analysis.Based on the results of data processing it is produced that there is a very high influence of the reward system with the principal's leadership on the teacher's performance of 0.937 with a determination rate of 87.79% with the multiple linear regression equation Y = 37.555 + 0.293x1 + 0.384x2).